On the Etymology of Lexemes with the Root ринд-/рынд- in the Northern Russian Dialects - Feoktistova, Lyubov A. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2021)
This article attempts to find out the origin of a number of homonyms, as well as their correlates (phonetic, lexical-semantic variants, and derived words), i.e ри́нда / ры́нда, ры́н(д)ега / ры́нюга, ринь / рынь, etc. They are recorded in the Northern Russian dialects in independent and related (as part of phraseological phrases) use in two areas, i.e. the north-western regions of Arkhangelsk region and Belozerye. The main source of dialect material is the card catalogue of the Dictionary of Dialects of the Russian North, which makes it possible to take into account a number of additional parameters during the etymologisation and semantic reconstruction of dialecticisms: the exact geographical reference, the number of fixations, etc. From the point of view of semantics, these dialecticisms can be divided into five groups: the natural sphere (meteorology), various spheres of human activity (fishing, cooking, clothing (with some conditionality)), as well as human behaviour. The linguistic geography data indicate the borrowed character of the lexemes and the Finno-Ugric languages as the source languages of borrowing. For the lexemes of each group, a source is found in the Finnic languages (Karelian and/or Veps) or Sami, taking into account information about the former settlement of the Finno-Ugric peoples in the specified territory, as well as the correlation и // ы and the origin of the phoneme ы in the dialecticisms studied.